Rigid water column model for simulating the emptying process in a pipeline using pressurized air (2018)
This paper presents a mathematical model for analyzing the emptying process in a pipeline using pressurized air. The rigid water column model (RWCM) is used to analyze the transient phenomena that occur during the emptying of the pipeline. The air-water interface is also computed in the proposed model. The proposed model is applied along a 271.6-m-long PVC-steel pipeline with a 232-mm internal diameter. The boundary conditions are given by a high-pressure air tank at the upstream end and a manual butterfly valve at the downstream end. The solution was carried out in a computer modeling program. The results show that comparisons between both the computed and measured water flow oscillations and gauge pressures are very similar; hence, the model can effectively simulate the transient flow in this system. In addition, the results indicate that the proposed model can predict both the water flow and gauge pressure better than previous models. © 2018 American Society of Civil Engineers.